Cover Vol. 20 No. 02 Desember 2023 - PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal Of Indonesia) (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2023)
Cover Vol. 20 No. 02 Desember 2023